Religiusitas Sebagai Intervensi Psikologis bagi Anak Autis: Kajian Fenomenologi - Ampun Bantali; Gadis Arniyati Athar (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2024)
This research explores the role of religiosity as a psychological intervention for autistic children. Religiosity, which includes faith, religious practices, and moral values, has been proven to support emotional stability, reduce anxiety, and improve the social relationships of autistic children. This research aims to describe the process of forming religiosity, analyze its impact on the psychological balance of children with autism, and identify supporting and inhibiting factors in its implementation. This research uses a qualitative phenomenological method, with data collected through in-depth semi-structured interviews and observations of students, teachers and parents at Special Schools (SLB) in Binjai City. Data analysis was carried out thematically to identify patterns and meaning of the subject's experiences. The research results show that religiosity develops through the dimensions of religious knowledge, religious practice, and the practice of moral values. These three dimensions have a positive impact on the emotional stability, social interaction and spiritual development of autistic children. Collaboration between teachers, parents and the community is an important factor in supporting the success of this process. However, limited teacher training and uneven parent involvement are challenges that must be overcome. This research concludes that religiosity is an effective psychological intervention approach in supporting the holistic development of autistic children. It is hoped that these results can become the basis for developing better inclusive education policies